Model characteristics of sensorimotor reactions and specific perceptions of trained wrestlers - Rostislav Pervachuk; Yuriy Tropin; Vyacheslav Romanenko; Anton Chuev (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to develop the model characteristics of sensorimotor reactions and specific perceptions of trained wrestlers. Material & Methods: analysis of scientific and methodological information, generalization of best practical experience, psychophysiological methods of research, methods of mathematical statistics. The study involved 26 trained wrestlers engaged in different kinds of wrestling (freestyle, Greco-Roman), aged 17 to 24 years old. Results: an assessment of simple, complex motor reactions and specific perceptions of wrestlers was performed. Based on the results obtained, the model characteristics of sensorimotor responses and specific perceptions of trained wrestlers. Conclusion: this analysis and the models presented were the basis for the development of evaluation criteria specific sensorimotor reactions and perceptions of the trained wrestlers.